Web-Based Personal Finance Management Application with Interactive Data Visualization: Aplikasi Manajemen Keuangan Pribadi Berbasis Web dengan Visualisasi Data Interaktif - Rahmatullah, Muhammad Wildan Jaffar; Oktavia, Nanda Nur; Lawrence, Lucas (Technomedia Journal, 2025)
Personal financial management plays a crucial role in achieving financial stability and ensuring effective control over individual finances. With the advancement of technology, more individuals are turning to digital solutions to manage their financial data more efficiently. This research focuses on the development of a web-based personal financial management application equipped with interactive data visualization tools, allowing users to easily track and analyze their income, expenses, and financial trends. Using the waterfall approach, this research includes the stages of design, development, testing, and implementation. The application is developed with Vue.js for the user interface and Highcharts for data visualization. Testing results show that the application effectively helps users understand their financial patterns and provides useful insights for financial decision-making. The testing results also indicate that the application makes it easier for users to plan their budget, identify unhealthy spending habits, and offer recommendations for savings. This application offers a more efficient solution compared to manual methods or traditional applications that only provide raw data without visual analysis. The conclusion of this research is that the developed application provides a practical and intuitive solution for personal financial management. The application helps users plan their finances wisely and make smarter decisions, thus improving financial literacy and supporting the achievement of their long-term financial goals. As a future development step, it is recommended to integrate machine learning and blockchain technology to enhance data security and transaction transparency.